Ca2+ sparks promote myogenic tone in retinal arterioles. (12th March 2013) - Kur, J; Bankhead, P; Scholfield, CN; Curtis, TM; McGeown, JG
<x xml:space="preserve">Abstract</x> Background and Purpose Ca2+ imaging reveals subcellular Ca2+ sparks and global Ca2+ waves/oscillations in vascular smooth muscle. It is well established that Ca2+ sparks can relax arteries, but we have previously reported that sparks can summate to generate Ca2+ waves/oscillations in unpressurized retinal arterioles, leading to constriction. We have extended these studies to test the functional significance of Ca2+ sparks in the generation of myogenic tone in pressurized arterioles. Experimental Approach Isolated retinal arterioles (25–40 μm external diameter) were pressurized to 70 mmHg, leading to active constriction. Ca2+ signals were imaged from arteriolar smooth muscle in the same vessels using Fluo4 and confocal laser microscopy. Key Results Tone development was associated with an increased frequency of Ca2+ sparks and oscillations. Vasomotion was observed in 40% of arterioles and was associated with synchronization of Ca2+ oscillations, quantifiable as an increased cross‐correlation coefficient. Inhibition of Ca2+ sparks with ryanodine, tetracaine, cyclopiazonic acid or nimodipine, or following removal of extracellular Ca2+, resulted in arteriolar relaxation. Cyclopiazonic acid‐induced dilatation was associated with decreased Ca2+ sparks and oscillations but with a sustained rise in the mean global cytoplasmic [Ca2+] ([Ca2+]c), as measured using Fura2 and microfluorimetry. Conclusions and Implications This study provides direct evidence that Ca2+ sparks can play an excitatory role in pressurized arterioles, promoting myogenic tone. This contrasts with the generally accepted model in which sparks promote relaxation of vascular smooth muscle. Changes in vessel tone in the presence of cyclopiazonic acid correlated more closely with changes in spark and oscillation frequency than global [Ca2+]c, underlining the importance of frequency‐modulated signalling in vascular smooth muscle.